Particle emissions measurements on CNG vehicles focusing on Sub-23nm. Issue 2 (1st February 2021) - Toumasatos, Zisimos; Kontses, Anastasios; Doulgeris, Stylianos; Samaras, Zissis; Ntziachristos, Leonidas
Abstract: The current study investigates the nonvolatile particle number emissions of three bi-fuel passenger cars (Euro 6b, 6d-temp ), which operate on compressed natural gas (CNG), as a primary fuel, and gasoline as a secondary one. The CNG fuel was injected into the engine using port fuel injection (PFI) while the gasoline fuel was either by PFI or by direct injection (GDI). A novel exhaust gas sampling and dilution system was employed for the determination of solid particle number (SPN) emissions at 10 nm (SPN>10nm ) and 2.5 nm (SPN>2.5 nm ). The vehicles were tested in the laboratory over different test cycles where the CNG solid particle number emissions greater than 23 nm (SPN>23nm ) were an order of magnitude lower than GDI and PFI gasoline emissions. However, when the size threshold was lowered to 10 nm or 2.5 nm, emissions were similar for both fuels. Particularly, SPN>2.5 nm emissions of the Euro 6 b vehicle exceeded the Euro 6 emission standard for both fuels while the SPN>23nm emissions were between 40 and 2.8 times lower than the limit for CNG and gasoline, respectively. Particle size distributions show a significant number of particles reside below the regulated limit of 23 nm, even lower than 10 nm. The results have significant implications in setting a particle number limit for alternative fuel vehicles while indicating that the current size threshold (23 nm) is insufficient for particle emission testing. Copyright © 2020 American Association for Aerosol Research